2021
DOI: 10.1155/2021/9935142
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori among Patients with Gastrointestinal Tract (GIT) Symptoms: A Retrospective Study at Selected Africa Air Rescue (AAR) Clinics in Kampala, Uganda, from 2015 to 2019

Abstract: Background. Helicobacter pylori (HP) infection is extremely common worldwide, with almost half of the world’s population infected. In Uganda, no study has been done on the trends of the prevalence of H. pylori infection in the affluent population. Therefore, this retrospective cross-sectional study aimed at determining the trend of H. pylori prevalence among affluent patients presenting with gastrointestinal (GIT) symptoms whose stool samples were tested at selected AAR clinics in Kampala area. Patients were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
5
2
2
Order By: Relevance
“…In this study, H. pylori infection was found in 34%, of dyspepsia patients with 95% CI (29.5% to 39.4%). This is in agreement with the result of the studies conducted in Colombia (36.4%) [12], Western Uganda (29.9%) [13], Gondar (37.6%) [7], Addis Ababa (36.8%) [14] and Uganda (35.7%) [15]. However, this finding is not comparable to studies conducted in Hosaena (51.4%) [16], Butajira, 52.4% [17], Nigeria (23.5%) [9] and Egypt (64.6%) [8].…”
Section: Plos Onesupporting
confidence: 92%
“…In this study, H. pylori infection was found in 34%, of dyspepsia patients with 95% CI (29.5% to 39.4%). This is in agreement with the result of the studies conducted in Colombia (36.4%) [12], Western Uganda (29.9%) [13], Gondar (37.6%) [7], Addis Ababa (36.8%) [14] and Uganda (35.7%) [15]. However, this finding is not comparable to studies conducted in Hosaena (51.4%) [16], Butajira, 52.4% [17], Nigeria (23.5%) [9] and Egypt (64.6%) [8].…”
Section: Plos Onesupporting
confidence: 92%
“…In this study, infections rise significantly among younger ages, and this is consistent with other investigations (Khoder et al, 2019;Namyalo et al, 2021). This may be because H. pylori bacterium is often acquired in childhood, especially when one of family members becomes infected with this bacterium then transmits it to others at an early age as a result of sharing food tools, and it can last for life [Namyalo et al, 2021;Weyermann et al, 2009;O'Ryan et al, 2015). This study showed that rates of H pylori infections are significantly higher in females and this is in line with other studies [(Al-Brefkani et al, 2021;Khoder et al, 2019, 28].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with other Iraqi and Arabic studies, because the highest rate of infection was among patients aged 20-30 years in Sulaimani, Iraq (Al-Windi., 2013), 16-18 years in Duhok, Iraq (Al-Brefkani et al, 2021, and age group of 30 years old in Emirates Arabia (Khoder et al, 2019). Other non-Arab studies have also found that rates of H. Pylori infections are rising in younger age groups (Syam et al, 2015;Namyalo et al, 2021). In this study, infections rise significantly among younger ages, and this is consistent with other investigations (Khoder et al, 2019;Namyalo et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the prevalence of anemia among H. pylori -infected individuals was higher at 11% compared to H. pylori -negative patient counterparts at 8.8%. This prevalence is higher than the reported prevalence of H. pylori infection in Bwera Hospital in Kasese, Uganda, by Tsongo et al at 29.9%, 18 in Kampala 35.7%, 19 27.3% in eastern Uganda 20 and 29.2% in Butembe Health Centre III Kyankwanzi district, Uganda.…”
Section: Discussioncontrasting
confidence: 55%